Development and Deployment of the Windbridge Psi and Related Phenomena Awareness Scale (WPRPAS) - Beischel, Julie; Boccuzzi, Mark (Journal of Scientific Exploration, 2020)
Surveys regarding anomalous beliefs and exceptional experiences are an important methodology in sociology and psi-related research. Previously published questionnaires, however, contain various limitations in their philosophy, language, and usefulness. This study aimed to develop a psi survey and collect data from an experience-centered perspective. Established survey development and piloting methods were used to create the Windbridge Psi and Related Phenomena Awareness Scale (WPRPAS), a novel 10-item web-based instrument which phenomenologically describes experiential phenomena without using problematic terms and asks respondents to signify whether they are aware of the phenomena or not and, if so, what experience they have had with them. For analysis, WPRPAS items were categorized as bidirectional which involve two or more people and can be given and/or received (energy healing, mediumship, and telepathy) or unidirectional which generally involve only the experiencer/respondent [clairvoyance, micro- and macropsychokinesis (PK), out-of-body experiences, near-death experiences, children’s memories of previous lives, and precognition]. Online survey response data were collected from self-identified mediums (n=316) and non-mediums (n=1,030) with no demographic statistical differences: 53.2 ± 10.1 and 53.9 ± 11.9 years of age, respectively; 89.5% and 85.5% female, respectively; both roughly 95% white. More than 80% of each participant sample reported being aware of all 10 phenomena. The portion of mediums who reported awareness of microPK and macroPK was significantly larger than the portion of non-mediums for those phenomena (each p<.00001). A significantly larger portion of mediums than non-mediums reported experiencing each of the 10 phenomena (all p<.0001). Ideally, the WPRPAS can be used by other researchers to assess awareness of psi and related phenomena and the prevalence of those experiences in other populations.